‘Experimental Homoeopathy’, Authored by Dr. Girish Gupta Released (Advancements in Homeopathic Research, 2022)
The book entitled ‘Experimental Homoeopathy’, authored by Dr. Girish Gupta, was released on 9th April 2022 by Shri Sarbananda Sonowal, Hon’ble Cabinet Minister of Ayush, Shipping and Waterways in Government of India in a scientific convention on the occasion of World Homoeopathy Day (WHD-2022) at Bharat Ratna C. Subramaniam Auditorium, New Delhi. Present on the dais were Dr. Munjpara Mahendrabhai, Hon’ble Minister of State (MoS), Ministry of Ayush and Ministry of Women & Child Development; Dr. Manoj Rajoria, Member of Parliament; Sri Vaidya Rajesh Kotecha, Secretary, Ministry of Ayush; Sri D. Senthil Pandiyan (IAS), Joint Secretary, Ministry of Ayush; Sri Pramod Kumar Pathak, Special Secretary, Ayush Education Policy; Dr. Sangeeta A. Duggal, Adviser (Homoeopathy), Ministry of Ayush; Dr. Anil Khurana, Chairman, National Homoeopathic Commission; Dr. Subhash Kaushik, Director General, Central Council for Research in Homoeopathy (CCRH), Dr. Subhas Singh, Director, National Institute of Homoeopathy (NIH) and Padamshree Dr. V. K. Gupta. This book is first of its kind in the homoeopathic world which is a compilation of various experimental research papers of Dr. Girish Gupta published in various journals. The book is broadly divided into two sections namely Virology and Mycology. It contains 16 experimental research papers- 6 on anti viral effect of homoeopathic drugs against plant & animal viruses and 7 on anti-fungal efficacy of these drugs against human pathogenic fungi. Additional 3 papers have been included on the evaluation of inhibitory effects of forbidden food items
Keywords: Experimental Homoeopathy; CCRH